Rapid shortening of survival duration in early fatal cases of COVID-19, Wuhan, China. (11th January 2021) - Nevels, Michael; Zhang, Yuzhou; Bambrick, Hilary; Tong, Shilu; Lambert, Stephen B; Hu, Wenbiao
Abstract: Severe COVID-19 cases place immediate pressure on hospital resources. To assess this, we analysed survival duration in the first 39 fatal cases in Wuhan, China. Time from onset and hospitalization to death declined rapidly, from 40 to 7 days, and 25 to 4 days, respectively, in the outbreak's first month.